2021
DOI: 10.1097/jsm.0000000000000721
|View full text |Cite
|
Sign up to set email alerts
|

Use of Supervised Exercise During Recovery Following Sports-Related Concussion

Abstract: To assess the safety of supervised exercise (SE) in acute sport-related concussion (SRC) and its influence on recovery. Design: Retrospective cohort study. Setting: University SRC clinic at a tertiary care center. Patients: One hundred ninety-four consecutive new patient charts were reviewed. Patients were included if they were seen within 30 days of sustaining a SRC, and their medical records included all required data elements. One hundred twenty-six patients were included in the analysis. Interventions: Sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The SECs were conducted as part of standard care for patients with SRC. 14 All SECs were led by an athletic trainer or physician in a dedicated exercise area of the clinic. The SEC did not occur until the patient's second visit to the clinic (ie, first follow-up visit).…”
Section: Supervised Exercisementioning
confidence: 99%
See 2 more Smart Citations
“…The SECs were conducted as part of standard care for patients with SRC. 14 All SECs were led by an athletic trainer or physician in a dedicated exercise area of the clinic. The SEC did not occur until the patient's second visit to the clinic (ie, first follow-up visit).…”
Section: Supervised Exercisementioning
confidence: 99%
“…Exercising within these guidelines has been considered safe and beneficial to recovery, even in the early symptomatic period. 8,14 The absence of symptom provocation during exercise was used as a sign of recovery to inform clinical decisions on initiating and completing a return-to-play protocol after concussion symptoms had resolved. 15,16 Whereas the standard protocols include a graduated course of aerobic and dynamic exercises, 1 it is notable that most exercise protocols studied for this purpose in a supervised clinic setting included only forms of basic aerobic exercise, such as the treadmill or stationary bike.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A different adolescent concussion clinic study reported that those with a “history of headaches or migraines” (36% of the entire sample) showed a higher likelihood of prolonged recovery at 30 days (OR = 4.02) ( 42 ). Adolescents with concussion seen in university settings did not have a higher likelihood of prolonged recovery ( 43 ) or greater time to return to play ( 44 ). In a study that examined adolescent and young adult athletes recruited from a hospital-based concussion program, those with a pre-injury history of migraines were not more likely to have a prolonged recovery (i.e., return to play > 60 days; n = 2/10, 20%) compared to those who did not have a pre-injury history of migraines ( n = 18/77, 23.4%; p = 0.83) ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to appreciate that only one study was designed specifically to examine migraine as a risk factor ( 45 ). All other studies included migraine as a secondary or exploratory variable; some studies discussed their rationale for examining pre-injury migraines ( 10 , 20 , 34 37 , 41 43 , 46 ), while others did not ( 13 , 14 , 16 19 , 21 , 30 , 32 , 33 , 38 40 , 44 ). Most studies ( n = 19/25, 76%) did not find a statistically significant association between having pre-injury migraines and a prolonged recovery or worse clinical outcome following concussion, two studies had both significant and null findings, and four studies showed only significant findings.…”
Section: Discussionmentioning
confidence: 99%